Ultra-low level optical detection of mercuric ions using biogenic gold nanotriangles - Singh, Amit; Pasrichax, Renu; Sastry, Murali (Analyst, 2012)
Mercury is a serious environmental pollutant known to have detrimental health effects in all life forms. Here, we report the use of biologically synthesized aqueous gold nanotriangles for sensitive and selective optical detection of femto-molar levels of mercury ions by exploiting the high amalgamation tendency of mercury metal towards gold. Aqueous chloroaurate ions were reduced using lemongrass (Cymbopogon flexuosus) leaf extract at room temperature to form gold nanotriangles. Mercuric (Hg2+) ions were reduced in the presence of these triangles to facilitate amalgamation and the optical properties were monitored. We observe a significant change in the longitudinal plasmon absorption band of the nanotriangles even at femto-molar concentrations of mercuric ions. High-resolution transmission electron microscopy confirms changes in particle morphology at such low concentrations. This protocol shows no sensitivity to other environmentally relevant metal ions, including Pb2+, Zn2+, Cd2+, Fe2+, Ni2+, Sr2+, Ca2+, Mn2+, and Cu2+, confirming further that change in the optical properties of gold nanotriangles in the presence of reduced mercuric ions is solely due to the strong amalgamation tendency of mercury metal.